Implementation of Husband's Obligations Post-Divorce (Case Study in Mutiara Timur District, Pidie Regency) - Ezi Azwar (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2022)
Mutiara Timur is one of the districts in Pidie Regency, Aceh Province. Divorce cases in this district are increasing every year. After the divorce, the exhusband is obliged to carry out several obligations to his ex-wife and children, but in practice the process of fulfilling the obligations of the ex-husband to the child and post-divorce wife has not been carried out properly. This type of research is field research, namely research that is directly carried out in the field or to respondents. In this study, the researcher used a qualitative descriptive analysis. And using an empirical-juridical approach, which is a legal research method that functions to be able to see the law in a real sense and examine how the law works in a community environment. The obligations of the ex-husband after the divorce are: to provide mut'ah, iddah rights, madhiyah maintenance, division of joint assets, paying off dowries owed, and providing a living for their children. After the author conducted research on 18 divorced couples, the author found that there were 13 ex-husbands who were obliged to provide for their children. Of the 13 ex-husbands, only two people carry out the obligation to provide maintenance for their children perfectly. There are 7 people who are obliged to give mut'ah and the right of iddah to the ex-wife. Of the 7 people, only one person is carrying out his obligations. There are 7 people who are obliged to carry out the distribution of joint assets. Of the 7 people, there are only two people who carry out their obligations. Meanwhile, there are 7 people who are obliged to pay for Madhiyah's living. Of the 7 people, there is not a single person who carries out his obligations. The factors behind the effective and ineffective implementation of husband's obligations after divorce in Mutiara Timur District include: economic factors, communication factors, education factors, remarriage factors, and divorce background factors.